Evolution of Magnetic Rayleigh-Taylor Instability into the Outer Solar Corona and Low Interplanetary Space - Mishra, S.K.; Singh, T.; Kayshap, P.; Srivastava, A.K. (Institute of Physics Publishing, 2018)
We analyze the observations from Solar TErrestrial RElations Observatory (STEREO)-A and B/COR-1 of an eruptive prominence in the intermediate corona on 2011 June 7 at 08:45 UT, which consists of magnetic Rayleigh-Taylor (MRT) unstable plasma segments. Its upper-northward segment shows spatio-temporal evolution of MRT instability in form of finger structures up to the outer corona and low interplanetary space. Using the method of Dolei et al., It is estimated that the density in each bright finger is greater than the corresponding dark region lying below it in the surrounding intermediate corona. The instability is evolved due to wave perturbations that are parallel to the magnetic field at the density interface. We conjecture that the prominence plasma is supported by tension component of the magnetic field against gravity. Through the use of linear stability theory, the magnetic field is estimated as 21-40 mG to suppress growth of MRT instability in the observed finger structures. In the southward plasma segment, a horn-like structure is observed at 11:55 UT in the intermediate corona that also indicates MRT instability. Falling blobs are also observed in both of the plasma segments. In the outer corona, up to 6-13 solar radii, the mushroom-like plasma structures have been identified in the upper-northward MRT unstable plasma segment using STEREO-A/COR-2. These structures most likely grew due to the breaking and twisting of fingers at large spatial scales in weaker magnetic fields. In the lower interplanetary space up to 20 solar radii, these structures are fragmented into various small-scale localized plasma spikes, most likely due to turbulent mixing. © 2018. The American Astronomical Society. All rights reserved..
Keywords: instabilities; corona; magnetic fields